Why do consumers buy recycled shoes? An amalgamation of the theory of reasoned action and the theory of planned behaviour - Yadav, Sher Singh; Kar, Sanjay Kumar; Rai, Prashant Kumar (Frontiers in Environmental Science, 2022)
The footwear industry's transition to a circular economy is a concern for sustainable development. The emerging recycled shoe production may lead to sustainable consumption in footwear industry. The consumers are now more cognizant of the negative effect of their shopping choice. We study the factors influencing consumers' intention of buying recycled shoes. We applied the Theory of Reasoned Action (TRA) and Theory of Planned Behaviour (TPB). As this is an emerging trend there is a dearth of sufficient literature regarding sustainable recycled shoe purchase behaviour. We aim to fill this broad gap with this empirical research. We found that perceived environmental knowledge, subjective norms, sustainable label awareness, and shoe choice motive influence attitude. Further, attitude, word of mouth, and environmental consciousness shape purchase intention. Sustainable label awareness, shoe surplus, and purchase intention affect purchase behaviour. The study is beneficial for policymakers and management of companies to make decisions related to footwear product positioning and targeting.